2015
DOI: 10.3382/ps/pev197
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ascites syndrome and related hematological response in short-term feed-restricted broilers raised at low ambient temperature

Abstract: Ascites is a major cause of mortality and morbidity in modern broiler production. Reduction of early growth, followed by compensatory gain, seems a practical and viable method to minimize losses caused by ascites. An experiment was conducted to determine if early feed restriction can reduce the incidence of ascites in broilers exposed to cool temperatures. Ross 308 cockerels (N=180) were assigned to 5 diet treatments and 2 temperature regimes, with 3 replicate pens of 6 birds per treatment and temperature. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 55 publications
2
12
0
4
Order By: Relevance
“…No significant differences were noted across bursa, thymus, spleen, or femur, suggesting no deficiency in those nutritional components that are required for proper development of lymphoid organs. This is consistent with previous research that showed that moderate decrease in CP level (range between 18 and 23%) had no effect on bursa, thymus, and spleen weight ( 19 , 28 , 29 ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…No significant differences were noted across bursa, thymus, spleen, or femur, suggesting no deficiency in those nutritional components that are required for proper development of lymphoid organs. This is consistent with previous research that showed that moderate decrease in CP level (range between 18 and 23%) had no effect on bursa, thymus, and spleen weight ( 19 , 28 , 29 ).…”
Section: Resultssupporting
confidence: 93%
“…Broilers fed an RCP diet tended to have lower body weight gain between d 1 and d 28 but compensated between d 28 and d 35 ( Table 3 ). This is consistent with previous research which has shown that reduced protein starter phase diets do not have a negative impact on performance, and also, lower body weight will be compensated after the fourth week ( 19 , 21 , 22 ). This is also consistent with prior reports which point to specific amino acid supplementation rather than CP as most critical to broiler performance.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…For the first seven days of the experiment, the temperature of both rooms was a constant 33 °C for the full 24 h in each day. From day 8, the temperature in each room was either TN where the temperature was decreased gradually from 33 °C to 25 °C on 21 days (one degree every two days starting from day 7) and then maintained at 25 °C from 21–42 days, which is in the range of the optimum temperature for Ross-308 broiler chickens [ 28 ] or HS conditions. The HS conditions were characterized as cyclic 33 °C from 1–42 days where the chickens were kept at 33 °C between 08:00 to 17:00 h and then the prevailing temperature in the TN room for the rest of the day.…”
Section: Methodsmentioning
confidence: 99%